Магнитные Fe−Co−Ni наночастицы, полученные восстановлением из смеси оксалатов - Кущевская, Н.Ф.; Перекос, А.Е.; Уварова, И.В.; Войнаш, В.З.; Ефимова, Т.В.; Польшин, Э.В.; Кущевский, А. Е.; Олешко, А.И.; Бабутина, Т.Е. (Видавничий дім "Академперіодика" НАН України, 2007)
Magnetic properties and dispersity of powders prepared by reduction of Fe, Ni, and Co from a mixture of oxalates in carbonaceous gas media have been studied using Mossbauer and small angle x-ray analyses and magnetic mapping. The influence of dispersity, morphology, and phase composition of the powders on their magnetic characteristics has been shown.